Impact of concept mapping on students’ critical thinking skills in Science - Fatin Azhana Abd Aziz; Lilia Halim (Penerbit Universiti Kebangsaan Malaysia, 2019)
The lack of students’ critical thinking skills has been a persistent problem in science education. This study aimed to identify the effectiveness of Collaborative Concept Mapping (CCM) and Individual Concept Mapping (ICM) in improving students’ critical thinking skills in science subjects. This study employed quasi-experimental research design that involved 189 form one students from public secondary schools in Malaysia. The manipulated variable in this study is teaching approaches, which includes Collaborative Concept Mapping (CCM), Individual Concept Mapping (ICM) and conventional method (CM). Meanwhile, the dependent variable is students’ critical thinking skills in Science. Data was collected using critical thinking skills diagnostic tests and analysed using one-way ANOVA test. The study showed that the level of critical thinking skills is significantly higher among students in CCM group in comparison to students in ICM and CM groups while there is no significant difference in students’ level of critical thinking skills in ICM and CM groups. This study indicated that CCM approach is effective in improving students’ critical thinking skills in Science, and thus should be integrated into Science classroom learning in secondary schools.